THE FUND OF LAND AS A SOURCE FOR INCREASING THE INCOME OF THE SPECIAL FUND OF THE MINISTRY OF DEFENSE OF UKRAINE - Syzov, A.; Kuzmenko, V. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The article analyses the state and development of the fund of land of the Ministry of Defense of Ukraine in the course of the years of Ukrainian independence in accordance with the data presented by the State geographical cadstre and the Ministry of Defense of Ukraine, particularly: the peculiarities of their extortion and return as a result of court investigations. The main issues of the circulation of land are presented, as well as the mechanism of its introduction and the fact that it is economically appropriate, together with ways for solving the issues mentioned. The order for assessing the value of land property has been determined and proven by arguments, both the necessity and effective methods of further using the lands of the Ministry with a perspective of increasing the possible income to the special fund of the Ministry of Defense of Ukraine by selling or leasing them. The most attractive method to increase the income of the special fund of the Ministry of Defense has been chosen due to the circulation of land used mentioned for defense purposes. The legal subjects to use the land, presented for defense purposes are military units, facilities, military-educational institutions, enterprises and organizations of the Armed Forces of Ukraine, other military formations, that are functioning as independent judicial entities. Pieces of land property to the mentioned subjects are usually given for permanent use. Regardless of the tasks and functions, the users of the land for defense purposes are responsible for, they enjoy and are entitled to overall rights granted to all the land users, and do also perform the appropriate duties concerning the assurance of rational using and the appropriate defense of land resources.